Exploring Plant-Microbe Interactions in Extreme Environments: Lessons from Arid and Desert Ecosystems - Enagbonma, Ben Jesuorsemwen; Imade, Emmanuel Edoghogho; Babalola, Olubukola Oluranti; Modise, David Mxolisi; Rigobelo, Everlon Cid [UNESP]; Cruz, Cristina (Springer Nature, 2025)
Desert and arid environments are among the harshest ecosystems on Earth, characterized by nutrient-deprived soils, extreme temperatures, and minimal rainfall. Despite these challenging conditions, these ecosystems support an impressive diversity of plant life, largely due to the intricate interactions between plants and microbes. Here, we presented insights into the dynamics of plant-microbe interactions in these extreme environments, shedding light on plant adaptation mechanisms and offering new approaches for ecosystem management and sustainable agriculture. This review is organized into four sections: (i) challenges of arid and desert environments, (ii) plant adaptations in arid and desert ecosystems, (iii) the role of microbes in plant adaptation, and (iv) lessons learned and applications. Exploring plant-microbe interactions in desert and arid environments reveals the remarkable resilience of life in extreme environments. By understanding the mechanisms through which plants and microbes coexist and cooperate under these conditions, we gain deeper insights into ecosystem dynamics and uncover new opportunities for innovation in agriculture and ecological management.